Correlation of cross-linking as measured by the trans-vinylene index and in vitro wear of polyethylene from various acetabular liner brands - Peter Wahl; Roman Heuberger; Andrea Pascucci; Thomas Imwinkelried; Markus Fürstner; Niels Icken; Michel Schläppi; Robin Pourzal; Emanuel Gautier (Bone & Joint Research)
Aims: Highly cross-linked polyethylene (HXLPE) greatly reduces wear in total hip arthroplasty, compared to conventional polyethylene (CPE). Cross-linking is commonly achieved by irradiation. This study aimed to compare the degree of cross-linking and in vitro wear rates across a cohort of retrieved and unused polyethylene cups/liners from various brands. Methods: Polyethylene acetabular cups/liners were collected at one centre from 1 April 2021 to 30 April 2022. The trans-vinylene index (TVI) and oxidation index (OI) were determined by Fourier-transform infrared spectrometry. Wear was measured using a pin-on-disk test. Results: A total of 47 specimens from ten brands were included. The TVI was independent of time in vivo. A linear correlation (R2 = 0.995) was observed between the old and current TVI standards, except for vitamin E-containing polyethylene. The absorbed irradiation dose calculated from the TVI corresponded to product specifications for all but two products. For one electron beam-irradiated HXLPE, a mean dose of 241% (SD 18%) of specifications was determined. For another, gamma-irradiated HXLPE, a mean 41% (SD 13%) of specifications was determined. Lower wear was observed for higher TVI. Conclusion: The TVI is a reliable measure of the absorbed irradiation dose and does not alter over time in vivo. The products of various brands differ by manufacturing details and consequently cross-linking characteristics. Absorption and penetration of electron radiation and gamma radiation differ, potentially leading to higher degrees of cross-linking for electron radiation. There is a non-linear, inverse correlation between TVI and in vitro wear. The wear resistance of the HXLPE with low TVI was reduced and more comparable to CPE. Cite this article: Bone Joint Res 2024;13(11):682–693.